Forecasting for Largest Earthquakes - Yegulalp, Tuncel M. (Management Science, 1974)
The primary concern of this paper is the establishment of a forecasting procedure for largest earthquake magnitudes of the next n years. It is shown that the use of the third-type asymptotic distribution of the largest values as an approximation to the exact distribution provides for an expression for the expected value and the mode of the largest earthquake magnitude in the next n years. An example of the application of this procedure is given and the results are compared with actual observations.